PENYAMAAN BATAS USIA PERKAWINAN PRIA DAN WANITA PERSPEKTIF MAQASID AL-`USRAH (ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 22/PUU-XV/2017) - Moch. Nurcholis (Institut Agama Islam Negeri (IAIN) Kediri, 2019)
Marital Age Arrangement as ruled by UU Perkawinan and KHI is part of open legal policy category and has legal validity according to regulation of Constitutional Court (Mahkamah Konsitusi). Nevertheless, legal policy must be positioned unexceeding authority, unbreaking morality and rationality of law, not to impact intolerable injustices, and not clearly contradicting Indonesian Constitution (UUD) 1945. Hence, relating to questioning phrases in article 7 verse 1 “in 16 years old” as part of Marital Law N. 1/1974. The Constitutional Court on its court decision explains that that provision is has not binding legal force. This decision has implicated obligation of equalizating minimum age of marriage (both male and female). Then, what is maqasid al-usrah thought on this decision? To answer that question, this research will explain criteria of adulthood from Islamic Law perspective and maqasid al-usrah thought on equalizating minimum age of marrige, both male or female. Islamic Law, throught its concept of baligh and `aqil, has opinion that measure of adulthood (both male and female) is same, where they have reached 15 years of age. Biologically, male is considered adult when he released sperm firstly. And female is considered adult when she menstruasting for the first time, or her sense of smell is more sensitive, or changing vocal sound, or growing some hair around her vagina and on armpits. Equalizating marital age between man and woman is justified based on maqasid al-usrah and Islamically legal as long as its purpose is implementing the marital goals